Studi Literatur: Implementasi Teori dan Pendekatan Konseling Sebaya Bagi Siswa - Yusuf Hasan Baharudin; Nikmah Maulina; Nafisatul Ulumil Mubarokah; Zainal Ngabidin; Ahda Naufal Nur Faiq (Program Studi Bimbingan dan Konseling, FKIP Universitas Pancasakti Tegal, 2022)
Peer counseling is a process of counseling services by peers to counselees to face their problems and apply them in everyday life. Adolescents are more likely to tell their problems to their peers than to their parents or teachers. This makes peer counseling effective in helping adolescents cope with their problems. Teenagers judge that adults will not be able to understand their feelings, and only their peers can understand them. Therefore, peer counselor intermediaries in the counseling process can help both the counselee and expert counselor in dealing with the problems experienced by the counselee.